Tourism Development and Community Welfare: A Case Study of Local Entrepreneurs around Selong Belanak Beach, Central Lombok, Indonesia - Ruslan Jayadi; Baiq Solatiyah (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study investigates the impact of tourism development on community welfare among local entrepreneurs operating around Selong Belanak Beach, Central Lombok, Indonesia. Using a qualitative descriptive approach, the research aims to understand how tourism growth influences socio-economic conditions, employment opportunities, and local business sustainability. Data were collected through interviews, observation, and documentation involving small business owners, local residents, and tourism stakeholders. The findings reveal that tourism development has significantly improved household income, increased employment, and encouraged the establishment of micro-enterprises such as food stalls, lodging, and handicraft shops. The multiplier effect of tourism has strengthened local entrepreneurship and reduced rural poverty. However, the study also identifies challenges, including environmental degradation, increased cost of living, and unequal participation between local and external actors. The results suggest that tourism should be managed through participatory and sustainable frameworks that integrate community involvement, environmental awareness, and local economic empowerment. By highlighting both positive and negative dimensions, this study provides insights for policymakers and practitioners to promote inclusive and sustainable tourism development that enhances community well-being.